2015
DOI: 10.1080/07391102.2015.1054431
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cd2+uptake ability of SmtA protein by Lys/Cys mutation; experimental and theoretical studies

Abstract: The improved Cd(2+) surface affinity characteristics of a mutated cyanobacterial metallothionein SmtA (K45C) were investigated via experimental and theoretical methods. Molecular dynamics simulations were carried out using a model of Cd(2+) and other ions enclosed in a fully hydrated simulation box with the wild-type or mutated SmtA protein. The theoretical results suggested that mutated SmtA was more powerful in absorption of Cd(2+) than the wild-type protein. Then, the mutated smtA gene (from Synechococcus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The uptake of metals is tightly regulated by metal-dependent transcription regulators to preclude the toxicity of excess metals (Saffar, Mehri, Mahnam, & Mobini-Dehkordi, 2015). SmtB/ArsR family metal-sensor proteins are transcriptional factors regulating the intracellular metal ion homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of metals is tightly regulated by metal-dependent transcription regulators to preclude the toxicity of excess metals (Saffar, Mehri, Mahnam, & Mobini-Dehkordi, 2015). SmtB/ArsR family metal-sensor proteins are transcriptional factors regulating the intracellular metal ion homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Friedman et al's study showed that a protein could sequester Na + ions [22]. Also, Saffar et al showed that a mutated SmtA protein could absorb cadmium ions [24]. In addition, experiments on ion Europium (III) absorption with the zwitterion form of amino acids by means of UV-Vis spectroscopy were studied by Heller et al [42].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, advances in computer technology and algorithmic improvements has made MD simulation a valuable tool in many areas of science, such as proteins or nucleic acids [21]. Currently, conventional MD simulations are being used to study the interactions between proteins and ions in dilute salt solutions [22][23][24].…”
mentioning
confidence: 99%